Ensino de ciências e atividades interativas e colaborativas: uma proposta de aprendizagem significativa crítica - Amaral, Adriana do (2018)
The current research investigates contributions from didactic strategies. These strategies were based on the development of interactive experiments by high school students, and their impact on critical learning was evaluated. This work used strategies based on interactive and collaborative activities, even though they were anchored in the autonomy from the developer of the knowledge subject, they were permeated by actions mediated with words. To reach the objective, activities about the theme “Water” were elaborated and implemented. These activities enabled the recognition from the variety of subjects involving Nature Sciences, as well as the discussion and creation of interactive experiments. Meetings were carried out with high school students from a federal public school, located in Rio de Janeiro. To gather the data, before and after conducting the activities, we employed a semi-structured interview and a conceptual map. The former was recorded for later transcription and analysis. In order to analyse the data, we applied the Content Analysis. Based on the analysis from the collected data, it was found that the proposed educational activities implemented have contributed for the autonomy development from high school students. Moreover, the students have learn in a significantly and critical manner. From the analysis content, it was possible to demonstrate the educational strategies suitability as relevant methodology for the quality improvement of science teaching, characterizing, therefore, as the product from this research.